Are we following the Art. 40.7 of the Code in letter and spirit? - Bandyopadhyay, Subir; Krishna, Gopal; Venu, Potharaju (Phytotaxa, 2014)
It was observed that authors of the names of new taxa, in some instances, fail to deposit holotypes in the herbaria stated in the protologues. Suggestions are invited to remedy the situation so that authors actually deposit holotypes in herbaria cited by them.